FINANCING BEHAVIOR OF THE PLANT OF SUGARCANE TO FARMERS IN BLITAR DISTRICT (Ethno methodology Study on Sugarcane Farmers in Rejoso Village, Binangun District, Blitar District) - Nurika Mauliyah; Arif Wahyudi (JARES (Journal of Academic Research and Sciences), 2018)
This research was conducted in Rejoso village, Binangun sub-district, Blitar district, with research object of sugar cane farmers there. This study aims to find out how the behavior of farmers in Rejoso Village about financing in the management of sugar cane, especially in financing behavior of the plant of sugarcane. In Rejoso village, plant of sugarcane is only done once in the period of 5 to 10 years because once planting sugarcane can be harvested many times even up to 10 times the harvest. The type of research used is qualitative research using Ethnomethodology method. Ethnomethodology is a study of how people create and understand their everyday life and the way they complete daily life. The subject for ethno methodology is not primitive tribal people but people of various situations in our own society. In this study, the subject of research is the sugar cane farmers in the Rejoso Village, Binangun District, Blitar. Data obtained by interview technique then result of the interview then analyzed to know how financing behavior of the plant of sugarcane. Based on the research results obtained from analyzing the results of interviews with sugar cane farmers in Rejoso Village that the financing behavior of the plant of sugarcane is vary depending on each individual. The difference in behavior lies in how to obtain sugar cane seeds, how to prepare the land and how to plant seeds of sugar cane.